Electrocoagulation treatment of dairy processing and slaughterhouse wastewaters. (March 2019) - Reilly, Matthew; Cooley, Andrew P; Tito, Duarte; Tassou, Savvas A; Theodorou, Michael K
Abstract: The dairy processing and slaughterhouse industries consume large volumes of water and their waste effluents often contain high levels of chemical oxygen demand (COD), biochemical/biological oxygen demand (BOD) and fertilising nutrients. Therefore, water treatment is necessary to reduce the levels of these contaminants prior to discharge or reuse of the water. In this short review paper we provide a brief overview of electrocoagulation (EC) technology and summarise the current literature relating to the use of EC treatment to clean dairy processing and slaughterhouse wastewaters.